Dynamics of Small Mobile Helium Clusters Near a Symmetric Tilt Grain Boundary of Plasma-Exposed Tungsten. (2nd January 2017) - Hu, Lin; Hammond, Karl D.; Wirth, Brian D.; Maroudas, Dimitrios
Abstract : We report the results of a systematic atomic-scale analysis of small helium cluster dynamics near a Σ3<111>{121} symmetric tilt grain boundary (GB) in tungsten based on molecular-dynamics simulations according to a reliable interatomic interaction potential. We find that small, mobile helium clusters (Hen, 1 ≤ n ≤ 7) in the near-GB region are attracted to the GB due to an elastic cluster-GB interaction force. Moreover, as the clusters drift toward the GB, cluster trap mutation (TM) reactions in the near-GB region are activated at rates much higher than those in the bulk of the material's grains. This near-GB cluster dynamics has significant effects on the near-GB defect structures and the amount of helium retained in the material upon plasma exposure. Each TM reaction generates a tungsten vacancy, which traps helium by forming an immobile helium-vacancy complex, and an interstitial tungsten atom in the form of an extended tungsten interstitial complex on the GB. This interstitial configuration is characterized by mobility that depends on the location where the TM reaction occurs: It is immobile when the vacancy produced by the TM reaction is located a few lattice planes away from the GB plane and highly mobile along a specific direction when the produced vacancy is located on the GB. The latter mechanism initiates a potentially fast migration path for W atoms along the GB toward a free surface, which may influence significantly the surface morphology of plasma-exposed tungsten.